The quarantine papers - Kalpish Ratna (New Delhi : HarperCollins Publishers India, 2010)
Ishrat Syed and Kalpana Swaminathan are surgeons. The anonym Kalpish Ratna is an almost anagram of their first names. This is their first Ratan/Ramratan Oak novel.--P.[407]
Novel.
Keywords: Novel English; Literaure English; Literaure